Trabalho de conclusão de ensino médio (TCEM): iniciação científica e abordagem investigativa na escola pública - Denise Maria Trombert Oliveira (2024)
Changes in the educational landscape and the challenges faced in teaching Biology demand a variety of teaching strategies from teachers to ensure effective student learning. In this context, inquiry-based learning emerges as a valuable tool to engage students in practices that facilitate both the assimilation and accommodation of knowledge. A notable practice is implementing the final project in high school (FPHS), which can significantly contribute to consolidating Biology concepts and those of other disciplines among students. However, this approach encounters specific challenges, leading to questions such as: How can FPHS be implemented in Brazilian public schools? What obstacles do students and teachers face throughout this activity? How can FPHS promote the development of critical thinking, scientific language, and writing through hypothesis formulation, conducting experimental and literature research, discussion, and conclusion of results? What are the potential benefits for students who, after FPHS, enter academic education? An inquiry-based didactic sequence (IB-DS) was developed and implemented to address these questions, comprising 15 classes, with Botany as the central theme. This sequence drew inspiration from a previous project conducted at a Vespasiano, Minas Gerais school between 2013 and 2017. During the IB-DS implementation, students were guided through the stages of the scientific method, from hypothesis formulation to presenting the results of their research, thus leading to scientific literacy. Research conducted with FP-HS graduates and teachers revealed a positive outcome from the practice, where both groups faced and overcame challenges. Significant experience from the process was evident among graduates, who reported confidence in facing academic education. In addition to the IB-DS, an e-book with detailed guidelines was developed as a pedagogical product so that other teachers can conduct FP-HS in their classrooms.